Geoarchaeological investigation of the Quriyat coastal plain (Oman). (10th November 2019) - Beuzen-Waller, Tara; Stéphan, Pierre; Pavlopoulos, Kosmas; Desruelles, Stéphane; Marrast, Anaïs; Puaud, Simon; Giraud, Jessica; Fouache, Éric
Abstract: Due to the richness of its coastal environments, particularly lagoons and mangrove, the low-lying areas of the Omani coastline attracted settlements very early. However, the low-lying coasts are highly mobile landscapes, whose evolution is controlled by multiple factors acting at different timescales, from episodic (extreme events) to millennial timescales (gradual shoreline changes). From a geoarchaeological analysis (geomorphological mapping, archaeological survey, core drilling, and sedimentological, faunic and microfaunic analyses), this study proposes for the first time to reconstruct the landscape evolution of the Quriyat coastal plain landscape during the Mid-Late Holocene. Results indicate a coastal landscape dominated by large lagoons and mangroves during the mid-Holocene (5th millennium). Between 6712 -6501 cal. BP and 6183−5992 cal. BP, an extreme wave event identified as a tsunami, is registered in the southern part of the coast. Between 4223−3984 cal. BP and 4150−3981 cal. BP, lagoons were quickly clogging over more than 3.5 km in favour of the development of sebkhas or dune fields. We suggest this rapid evolution is related to erosional crises linked to the setting up of arid conditions in this part of the Omani coast. The production of several sea-level index points shows a great stability of the relative sea-level over the last 6.000 yearscal. BP and point out the predominant role of sedimentary infilling in the coastline evolution of Quriyat. The high sedimentation rates, added to the exposure of coastal hazards, partially explains the relatively low density of archaeological sites found in the Quriyat coastal plain, despite the presence of major shell-midden (Khor Milk I and II), which attest the old attractiveness of this sector. From geoarchaeological and taphonomic points of view, the Quriyat area is considered as having non-favourable conditions for the preservation of archaeological remains.